Fame of the ‘Godly’ and ‘Ungodly’ People Against Envy — in Fabian Birkowski’s Funeral Preach Pamięć sprawiedliwego - Poterała, Paulina (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The aim of the article was to discuss the influence of jealousy (phthonos) on the fame of godly andungodly people and to present two divergent views on the posthumous fate, which Birkowski describedwith regard to three aspects: physical, religious and metaphysical – death in people remembrance.Furthermore, the character of dead Jan Wjeher is shown as an example of a godly person, who thanksto his deeds earned a fair physical death, eternal life and unquestionable fame.The work presents Birkowski’s funeral preach not only as Wejher’s life and death apotheosis, but alsoas a didactical idea, orienting listeners and readers to live their lives according to God’s orders. Orders,which ensure the avoidance of painful death, divine condemnation and human envy.